OBJECTIVE, SUBJECTIVE FINANCIAL LITERACY INFLUENCE ON COGNITIVE STYLE AND FINANCIAL RISK PERCEPTION - Aren, Selim; Akgunes, Ahmet Oguz (FUTURE ACAD, 2019)
Personality traits of individuals are one of the important variables that affect their thinking structures and behaviors. Personality traits are genetically formed. However, socialization and education affect the personality characteristics of individuals. Therefore, many studies have been done on collecting information, evaluating this information and making decisions. However, studies that reveal the effect of personality traits on financial decisions are much newer and few. In this study, the effect of financial risk perception was investigated based on cognitive style personality traits and Myers-Briggs style personality dimensions. Also, the effect of both objective and subjective financial literacy on this relationship is examined This study with this dimension has unique feature. As a result of the analysis, individuals with systematic style have a higher risk request at statistically significant level than individuals with other styles. In addition, it has been found that individuals of all styles and dimensions evaluate subjective financial literacy levels about %60 more than real financial literacy levels. (C) 2019 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Behavioural finance; cognitive style; risk perception; objective financial literacy; subjective financial literacy; INTUITION; Business & Economics